(untitled) (Cardiovascular Journal, 2012)
Background: People with metabolic syndrome are twice as likely to die from, and three times as likely to have a heart attack or stroke compared with people without the syndrome. People with metabolic syndrome have a five-fold greater risk of developing type 2 diabetes. We investigated the prevalence of metabolic syndrome in patients with newly diagnosed diabetes mellitus. Methods: It was a cross sectional study. The study was conducted in Department of Biochemistry, Sylhet MAG Osmani Medical College, Sylhet & Diabetic Hospital, Sylhet. The study was conducted From July 2008 to June 2009 among 200 patients with newly diagnosed type 2 diabetic patients with age >20 years. Along with blood glucose, different components of metabolic syndrome was assessed, i.e. serum triglyceride level, serum HDL level, blood pressure and waist circumference. Results- Prevalence of metabolic syndrome was 73.5% according to NCEP-ATP III criteria, 81.0% according to modified NCEP-ATP III criteria, 82.5% according to modified WHO criteria and 61.0% according to IDF criteria. All variables other than waist hip ratio and fasting blood sugar had statistically significant higher mean values among patients with metabolic syndrome than patients without metabolic syndrome. Conclusion: It may be concluded that prevalence of metabolic syndrome is considerable in newly diagnosed type 2 diabetic patients in our population. The considerable prevalence of metabolic syndrome in our population is implicative of an alarming risk of cardiovascular disease in future. Keywords: Metabolic syndrome; Type II diabetes mellitus. DOI: http://dx.doi.org/10.3329/cardio.v4i1.9385 Cardiovasc. J. 2011; 4(1): 17-25